Uruguay : Second Review Under the Stand-By Arrangement, Requests for Modification and Extension of the Arrangement, and Waiver of Nonobservance and Applicability of Performance Criteria, and Exchange System - Staff Report; Staff Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uruguay. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines Uruguay's Second Review Under the Stand-By Arrangement, Requests for Modification and Extension of the Arrangement, and Waiver of Nonobservance and Applicability of Performance Criteria and Exchange System. Progress on the structural front has been mixed. The macroeconomic framework is based on a return to economic growth. Notwithstanding the risks to the program, the IMF staff recommends completion of the second review and approval of the authorities' requests for waivers, extension of the arrangement, and rephasing of purchases.